Training approach-avoidance of smiling faces affects emotional vulnerability in socially anxious individuals - Rinck, Mike; Telli, Sibel; Kampmann, Isabel; Woud, Marcella L.; Kerstholt, Merel; te Velthuis, Sarai; Wittkowski, Matthias; Becker, Eni S. (Frontiers in Human Neuroscience, 2013)
Previous research revealed an automatic behavioral bias in high socially anxious individuals (HSAs): Although their explicit evaluations of smiling faces are positive, they show automatic avoidance of these faces. This is reflected by faster pushing than pulling of smiling faces in an Approach-Avoidance Task (AAT; Heuer, Rinck, & Becker, 2007). The current study addressed the causal role of this avoidance bias for social anxiety. To this end, we used the AAT to train HSAs, either to approach smiling faces or to avoid them. We examined whether such an AAT training could change HSAs’ automatic avoidance tendencies, and if yes, whether AAT effects would generalize to a new approach task with new facial stimuli, and to mood and anxiety in a social threat situation (a video-recorded self-presentation). We found that HSAs trained to approach smiling faces did indeed approach female faces faster after the training than HSAs trained to avoid smiling faces. Moreover, approach-faces training reduced emotional vulnerability: It led to more positive mood and lower anxiety after the self-presentation than avoid-faces training. These results suggest that automatic approach-avoidance tendencies have a causal role in social anxiety, and that they can be modified by a simple computerized training. This may open new avenues in the therapy of social phobia.